Lay epistemic theory and its cognitive-motivational approach to knowledge - Jaume, Luis Carlos (2021)
Lay epistemic theory has offered several contributions to the field of both epistemology and social cognition. This theory offers an epistemic framework, which is influenced by both cognitive and motivational factors. Within the motivational factors are the concepts of openness to new experiences and imperviousness to alternative explanations, which are encompassed by Webster and Kruglanski in the construct of need for cognitive closure. This construct explains both the motivational aspects of decision making and the interface between the cognitive and motivational properties of the individual in the process of acquiring knowledge and beliefs. In addition, the lay epistemic approach also encompasses the study of attributional processes and the effects of social interactions on epistemic activities. The purpose of this paper is the theoretical analysis of the lay epistemic model and its importance in epistemology by determining not only the cognitive aspects, but also the motivational aspects of the individual, on which knowledge is derived.